CONCEPT-BASED LEARNING AND ENHANCEMENT OF METACOGNITION IN NURSING EDUCATION - Hice, Diane L. (Acta Scientiae et Intellectus, 2024)
A concept-based curriculum uses overall principles with broad perspectives and applies them to relevant scenarios. In contrast to content-focused instruction, these broader-based concepts can have wide-reaching applicability. Concept-based attributes such as problem-solving, analysis, mapping, and critical thinking can reinforce metacognitive skills and promote higher-order thinking. These constructs are of particular importance to the provision of quality nursing care. A review of the literature was conducted to explore concept-based learning and how it informs metacognition in nursing education. Further experience, research and faculty education is needed to demonstrate the success of content-based learning, its influence on metacognitive development, and, most importantly, its promise to ensure safe, high quality patient care.